Precise nutrition 1: Standardization of the KOH protein solubility test for soybean meal in a single commercial laboratory and correlation to in vivo poultry amino acid digestibility - Nelson Ruiz; Carl M. Parsons; Brian Steinlicht; Dave Taysom; Xin Wu; Fiona Liu (Journal of Applied Poultry Research)
Summary: The KOH protein solubility (KOHPS) method to evaluate if a lot of commercial soybean meal (SBM) has undergone the Maillard reaction during processing was introduced to the animal feed industry by Araba and Dale (1990). Although it is used worldwide, there are 2 limitations that have not been addressed. There is large inter-laboratory variability of the test and an absence of a quantitative interpretation of the results in terms of amino acid (AA) digestibility that can be used by nutritionists and formulators for commercial SBM affected by the Maillard reaction. The objective of this study was to standardize the KOHPS method in a single commercial laboratory starting from the description by Araba and Dale (1990) by using commercial SBM samples whose in vivo AA digestibility status was known. For this purpose, 2 SBM samples, one with high solubility (80 to 85 % KOHPS) and another with low solubility (KOHPS ∼ 50 %), were used as reference samples to develop a preliminary protocol. Then adjustments in intensity of agitation were made with 4 SBM samples of known in vivo digestible Lys coefficients (0.88 to 0.96) to yield KOHPS values from 80 % to 85 %. The standardized protocol yielded KOHPS values from 50 to 56 % for the low solubility SBM reference sample and 3 samples known to have low in vivo digestible Lys coefficients (0.73 to 0.77). In conclusion, a standardized protocol is now available for the determination of KOHPS of commercial SBM that will allow regression equations to be developed for the estimation of digestible AA.